Andrographis paniculata Ethanolic Extract Improved Doxorubicin-induced Cardiac Inflammation, Alterations in Liver Function Parameters and Anemia - Eziefule, Oluebube Magnificient; Arozal, Wawaimuli; Wanandi, Septelia Inawati; Louisa, Melva; Wuyung, Puspita Eka; Dewi, Syarifah; Nafrialdi, Nafrialdi; Dewi, Yulia Ratna; Nabillah, Deya Adiby (Molecular and Cellular Biomedical Sciences, 2024)
Background: Doxorubicin (DOX), an efficacious chemotherapy drug is compromised by cardiotoxicity, myelosuppression, and hepatotoxicity. Due to the limited success of current treatments for DOX toxicity, there is a pressing need to explore alternative medical interventions, particularly from plant sources. This study was conducted to investigate the potential protective effect of ethanolic extract of Andrographis paniculata leaves (EEAP) against DOX-induced cardiac inflammation, liver toxicity, and anemia.Materials and methods: Sprague-Dawley rats were intraperitoneally injected with DOX at a total dose of 16 mg/kgBW. EEAP was administered orally for 4 weeks at doses of 125, 250, and 500 mg/kgBW/day according to the assigned treatment groups. The mRNA expression levels of interleukin-1β (IL-1β) and nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 (NLRP3) in the heart tissue, along with the concentrations of nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) and calcium level were examined. Additionally, the hematological parameters (including hematocrit, hemoglobin and red blood cells (RBCs)), aspartate aminotransferase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), and malondialdehyde (MDA) levels in blood were also analyzed.Results: EEAP dose-dependently decreased the mRNA expressions of IL-1β (p<0.05), tended to decrease mRNA expression of NLRP3 and the concentrations of NFκB and calcium in heart tissue compared with the DOX-only group. Additionally, EEAP dose-dependently decreased ALP values (p<0.0001) and tended to improve hematological parameters, as well as AST and MDA levels in serum.Conclusion: This extract may prevent DOX-induced cardiac inflammation, anemia, and hepatotoxicity. However, further studies are needed to confirm these findings, including the efficacy profile of the extract in cancer rats treated with DOX.Keywords: doxorubicin, Andrographis paniculata, inflammation, anemia, hepatotoxicity, herbal medicine